Mediation as an effective tool for resolving sports disputes - Shair Mohamad, Mohd Akram; Kamarudin, Abdul Rani (International Journal of Business, Economics and Law - IJBEL, 2015)
The relation to the infinite variety issues sprouting in sports or lex sportiva, like lex mercatoria in the early centuries, has now come of age and even begun a maturing process in the past thirty-five years or so. Lex sportiva now straddles sports management, sports medicine, tort, criminal law, employment contract, competition law and a host of multifarious activities related to sports. This has catapulted a host of legal issue and problems, demanding urgent legal solutions to actual or potential disputes. This paper briefly discusses the nature and development of lex sportiva, and how it is able to resolve sports disputes.Resolving sports dispute via the tiresome, dilatory and expensive process of litigation is most unsuitable. Arbitration may not be equally a satisfactory solution. The paper strongly advocates the far the most effective and resolution friendly mode of settling sports disputes is mediation. In support it highlights numerous advantages mediation has to offer.